2017
DOI: 10.1021/acsami.7b14236
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Nanosized Silicon Carbide-Rich Composite Coatings Produced by Noble Gas Ion Mixing

Abstract: Ion beam mixing has been used to produce a silicon carbide (SiC)-rich nanolayer for protective coating. Different C/Si/C/Si/C/Si(substrate) multilayer structures (with individual layer thicknesses falling in the range of 10-20 nm) have been irradiated by Ar and Xe ions at room temperature in the energy and fluence ranges of 40-120 keV and 1-6 × 10 ion/cm, respectively. The effects of ion irradiation, including the in-depth distribution of the SiC produced, was determined by Auger electron spectroscopy depth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
(54 reference statements)
1
23
0
Order By: Relevance
“…The detailed description of the conditions of the corrosion test can be found in ref ; its brief summary is as follows. The SiC-rich layer started to grow at the interfaces and its thickness depended on ion irradiation conditions such projectile, energy, and applied fluence and on the layer structure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed description of the conditions of the corrosion test can be found in ref ; its brief summary is as follows. The SiC-rich layer started to grow at the interfaces and its thickness depended on ion irradiation conditions such projectile, energy, and applied fluence and on the layer structure.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the 20–20 and 10–20 samples, only a part of the top C layer was consumed by the IBM-induced compound formation and thus the sample surface contained a carbon layer of various thicknesses. Therefore, before the corrosion test this upper carbon layer was removed by means of oxidation in microwave plasma at 500 °C for 10 min …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this 2D pattern, a 3D structure can be made utilizing the different chemical entities on the surface; the etching and/or oxidation rates of the SiC rich region is strongly different from those of Si and C [22,25]. E.gs, by etching the sample in HF/HNO3 solution for 10 min the pristine silicon layer is removed while the SiC rich region remains untouched resulting in a hole with a diameter determined by the arrangement of the SiO2 spheres (typically 600 nm) and a depth of 20 nm.…”
Section: Langmuir-blodgett Technique + Ibmmentioning
confidence: 99%
“…Recently we have shown that it is possible to produce SiC nano-coating at room temperature by applying IBM on C/Si multilayer structures [20][21]; the produced coatings exhibited excellent corrosion resistance properties [22]. The simultaneous application of masks and ion irradiation on a properly chosen C/Si multilayer system would lead to one step compound and pattern formation.…”
Section: Introductionmentioning
confidence: 99%